(untitled) (Research, Society and Development, 2021)
Objective: It aims to carry out the description of the data provided by the Ambulatory Information System on urgent care, describing the relevance and role of nursing. Methods: This is a descriptive study with a quantitative approach. A time series analysis of emergency care in the State of Minas Gerais, from January to December 2019, was carried out through the Ambulatory Information System. Results: Through the analysis of the data, it was possible to observe variations in the amount of emergency calls, in relation to the same ones performed by professional nurses and in terms of calls by level of complexity, with emphasis on the month of December. Conclusion: It is necessary to value nursing professionals, strengthen Primary Care as a gateway to the health system and promote health education, clarifying the responsibilities of each service.